Investigating Language Learning Autonomy And Foreign Language Classroom Anxiety Among Jordanian EFL University Students - Zreagat, Misarah Husny (2012)
The present study is regarded as a cross-cultural validation of the two constructs of foreign language anxiety and language learning autonomy. In the field of second language acquisition, research acknowledges that both cognitive and affective factors within a language learner affect the level of success achieved in learning a second language (L2). Among the affective variables that have received attention during the last few decades are language anxiety and learning autonomy. This study sought to investigate the levels of English language anxiety and English language learning autonomy among Jordanian EFL students in Yarmouk University, Jordan.